Between Human and Virtual Idol: Fans Reception Analysis of Digital Alter Ego Concept - Damar Rizky Nuranda; Mashita Phitaloka Fandia Purwaningtyas (Universitas Muhammadiyah Yogyakarta, 2023)
The emergence of K-pop idol group Aespa has changed the landscape of K-pop fan culture since the group introduced the concept of a digital alter ego in the form of digital “ae” members. This research aims to understand how Indonesian fans construct the meanings of the digital alter ego concept carried by Aespa. This research is conducted by the reception analysis method. Informants consisted of four Aespa’s fans, each with distinct experience as K-pop fans. The main findings in this research revolve around the different reading positions held by informants, as affected by the distinct framework of knowledge, relations of consumption, and technical infrastructure surrounding their cultural practices as K-pop fans. Aespa’s digital alter ego could be seen in three ways: as another version of the self, a dishonest self-representation, and a polished version of the self. Through these differences, it can be concluded that fans’ construction of meanings cannot be reviewed through a deterministic approach but through a socio-cultural approach instead.